Sonata 1980 para violino de Ernst Mahle: uma abordagem interpretativa visando a construção de uma performance - Souza, Ana Paula Gomes de (2017)
The compositional work of Ernst Mahle, german composer, naturalized Brazilian, becomes peculiar by original being turned to pedagogical practice. His compositions were initially created from the search for an accessible repertoire within the technical development of the students of numerous instruments. As a teacher and conductor, being one of the founders of the School of Music of Piracicaba / SP5, the present city where he reside, include in his works the elements of brazilian folk music, in parallel with the compositional influences of Bartók, who also use folkloric characteristics in your works. In the period between 1955 and 1980, Mahle composed Sonatas and Sonatinas for violin, of which this article presents the Sonata 1980 in an interpretative approach to construction of a performance, through reflections on contemporary music and contemporary brazilian music. From the contextualisation of the current music, it begins an approach on the construction of the performance and as stages of the execution in the technical, aesthetic and philosophical concepts, as well as a reflection on the practice of the interpretation. The biographical experience with the composer and shared through reports, post-interviews, resulting in a visit to his residence in the city of Piracicaba / SP on November 8, 2015. A maturation of this research development resulted in a performance construction, between technical and interpretative suggestions for a good performance, assisting a reflection on an appreciation of the contemporary repertoire of brazilian violin pieces not yet covered in recitals and concert halls.